The Effectiveness of the Implementation of Local Regulations on Muslim Women's Clothing In Encouraging Implementation of Islamic Teachings: A Case Study At State Senior High School 5 In Padangsidimpuan City - Mhd. Nur Husein Daulay (AT-TAFAHUM: Journal of Law, 2017)
The effectiveness of implementing regional regulations on Muslim clothing for men and women in encouraging. The implementation of Islamic teachings (Case Study at State Senior High School 5 in Padangsidimpuan City) is a study of regional autonomy or decentralization starting from the division of authority from the central government to regional governments. This regional regulation is a response to the real conditions related to the decline in morality and ethics of students, especially in senior high schools. This study describes the problem in detail. comprehensive, holistic, integrative, as a characteristic of qualitative research. Research is focused on understanding the effectiveness of implementing the use of Muslim clothing for men and women using a public policy approach as a tool for analyzing policy. The focus of this policy's target audience is: school students and educational units as implementers and supervisors of the policy. (2) The outline of the Padangsidimpuan city government's policy formulation regarding the use of Muslim clothing for men and women cannot be separated from key actors (key actors) involvement stakeholders and cross-party advocacy in the policy-making process and mechanisms implementation. (3) The implementation of the policy is running well.